Liver-Brain Axis in Sporadic Alzheimer’s Disease: Role of Ten Signature Genes in a Mouse Model - Jakhmola-Mani, Ruchi; Islam, Anam; Katare, Deepshikha P. (CNS & Neurological Disorders - Drug Targets, 2021)
Aim: Poor nutritional effect of junk food induces injuries to the liver and the brain but still most of the developing nations survive on these diets to compensate for the fast-paced lifestyle. The aim of the study is to infer the protein-connections behind the liver-brain axis and identify the role of these proteins in causing neurodegenerative disorders. Background: Chronic consumption of fructose and fat-rich food works as a toxin in the body and has the ability to cause a negative metabolic shift. Recently a study was published in Annals of Internal Medicine (2019) citing the loss of vision and hearing in a 14-year-old boy whose diet was strictly restricted to fries and junk-food for almost a decade. This puts the entire body on insulin resistance and related co-morbidities and causes simultaneous damaging effects on the liver as well as the brain. This work provides insights into the liver-brain axis and explains how the liver is involved in brain related disorders. Objective: In this study, transcriptomic data related to chronic eating of junk-food was analyzed and simultaneous damage that happens in the liver and the brain was assessed at the molecular level. Methods: Transcriptomic study was taken from the GEO database and analysed to find out the genes dysregulated in both the liver and the brain during this metabolic stress. Cytoscapev3.7 was used to decipher the signalling between the liver and the brain. This connection between both is called as the liver-brain axis. Result: The results obtained from our study indicate the role of TUBB5-HYOU1-SDF2L1-DECR1- CDH1-EGFR-SKP2-SOD1-IRAK1-FOXO1 gene signature in the decline of concurrent liver and brain health. Dysregulated levels of these genes are linked to molecular processes like cellular senescence, hypoxia, glutathione synthesis, amino acid modification, increased nitrogen content, synthesis of BCAAs, cholesterol biosynthesis, steroid hormone signalling and VEGF pathway. Conclusion: We strongly advocate that prolonged consumption of junk food is a major culprit in brain related disorders like Alzheimer’s disease and propose that receptors for brain diseases lie outside the brain and aiming them for drug discovery and design may be beneficial in future clinical studies. This study also discusses the connection between NAFLD (non-alcoholic fatty liver disease) and sAD (sporadic Alzheimer’s disease) owing to liver-brain axis.
Keywords: NAFLD